Islam Nusantara Sebagai Upaya Kontekstualisasi Ajaran Islam Dalam Menciptakan Moderasi Beragama - HS, Muhammad Alwi (Universitas Islam Negeri Raden Intan Lampung, 2021)
This article will contextualize the teachings of Islam from Arabic to Indonesia by linking them to the Islam Nusantara. This article will also show the moderate Islamic style displayed by Islam Nusantara. As for analyzing, this paper uses a descriptive-analytical method using contextualization theory, namely the search for understanding of Islamic teachings by involving context, as a knife of analysis. Some of the research results achieved by this paper are the contextualization of Islamic teachings from Arabic to Indonesia that has been carried out since the early spread of Islam in Indonesian soil as practiced by Walisongo. The spread of Islam in Indonesia did not bring about Arabic discourse, but found Islamic teachings (God's message) that were spread in Arab society, then applied in the context of Indonesian society. Furthermore, Islam Nusantara always displays the true spirit of Islam, spreads Islam peacefully, is tolerant of the differences faced, and maintains a wushta (moderate) attitude in addressing life's problems.